2011
DOI: 10.4067/s0718-58392011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of medicinal plant extracts against phytopathogenic fungus Alternaria spp

Abstract: The aim of the study was to evaluate the antifungal activity of extracts of 10 plant species used in traditional Uruguayan medicine against the phytopathogenic fungus Alternaria spp. The plants were selected on the basis of their reported ethnobotanical uses. Aqueous, saline buffer and acid extracts of different plant species were screened in vitro for their antifungal activity against Alternaria spp. For the antifungal evaluation we used a microspectrophotometric assay. Minimal inhibitory concentration (MIC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 26 publications
8
104
0
3
Order By: Relevance
“…The quantitative phytochemical analysis of the ethanol extracts of M. macrostachyum leaves revealed that there were high yields of alkaloids, flavonoids and saponins from the ethanol extracts from leaf of M. macrostachyum. The potency in the activeness of the constituents in the plant extracts justified the claims by several scientists that have identified the role of phytochemicals in the inhibition of fungi responsible for spoilage of food (Dellavalle et al, 2011;Cabral et al, 2013;Rakholiya et al, 2014;Negi and Chaturvedi, 2016). The analyzed compounds via GC/MS and HPLC fingerprinting showed constituents in the plants at its crude level and these might be responsible for the inhibition of test isolates.…”
Section: Discussionmentioning
confidence: 83%
“…The quantitative phytochemical analysis of the ethanol extracts of M. macrostachyum leaves revealed that there were high yields of alkaloids, flavonoids and saponins from the ethanol extracts from leaf of M. macrostachyum. The potency in the activeness of the constituents in the plant extracts justified the claims by several scientists that have identified the role of phytochemicals in the inhibition of fungi responsible for spoilage of food (Dellavalle et al, 2011;Cabral et al, 2013;Rakholiya et al, 2014;Negi and Chaturvedi, 2016). The analyzed compounds via GC/MS and HPLC fingerprinting showed constituents in the plants at its crude level and these might be responsible for the inhibition of test isolates.…”
Section: Discussionmentioning
confidence: 83%
“…Increasing regulations on the use of synthetic fungicides, build-up of chemical residues on the fruit and the emergence of pathogen resistance to the most frequently used fungicides, validate the search for novel biological control strategies. 1 In recent years, a number of plant extracts, their essential oils and their volatile components have been reported to have strong antifungal activity. 2 In the agricultural sector, plant extracts, essential oils and their components are gaining increasing interest as a result of their volatility, reasonably safe status, eco-friendly and biodegradable properties, and wide consumer acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…In Uruguay, Diaz-Dellavalle et al determined that aqueous extract of 10 plant species exhibit anti-fungal activity against Alternaria spp. [26]. Aqueous extract of both mature and immature fruits of our study had no effect on C. albicans compared to alcoholic extracts, so it may be some plant compounds such as phenols and alcohols have more anti-fungal potency than other types of extract [2].…”
Section: Discussionmentioning
confidence: 96%